Parasitological findings and antiparasitic treatment of captive Jaguarundis Herpailurus yagouaroundi (Carnivora: Felidae) in a conservation center in Brazil - Grossmann, Nárjara Veras; de Sousa, Anderson Silva; Cardoso, Rebecca Martins; Hoppe, Estevam Guilherme Lux [UNESP] (My University, 2018)
Ex situ management of wildlife provides a possibility for species maintenance, research development and environmental education. But as captive facilities are usually much smaller than the area occupied by a species in the natural habitat, cleaning might be insufficient, domestic species such as cats might be in close proximity, and wild animals in captivity are inevitably stressed, animals kept in these facilities are more at risk of acquiring parasitic infections. Therefore, an appropriate prophylactic protocol and consequent anti-parasitic therapy of affected animals are fundamental for any wildlife conservation center. This report describes the procedures adopted in a conservation center for wild felines in which four adult Jaguarundis were diagnosed with severe infection with gastrointestinal parasites and flea infestation. Two animals died and based on the necropsy findings and fecal examinations, infections with Ancylostoma caninum and Toxocara cati were diagnosed, as well as severe infestations with Ctenocephalides felis felis fleas, all common parasites of domestic cats. We discuss the applied therapy and the adopted environmental management, along with the importance of regular health assessments and a preventive medicine program for this species in captivity.
Keywords: Ancylostoma; Captivity; Ctenocephalides; Toxocara; Wild felines